Analysis Of the Influence of The Work Environment on Employee Health in The Production Process Uses FMEA And SEM Methods - Dinda Okta Dwiyanti Ridwan Gucci; Muhammad Adi Sukma Nalendra (JTI: Jurnal Teknik Industri, 2025)
Industrial transformation at the moment this is very impactful for development technology periodically large and complex. Development this industrial technology usually called industry 4.0. Industrial revolution 4.0. influence the world of business even. The industrial revolution had an impact on aspects life humans, including in the field occupational safety and health (K3). PT. XYZ is company fiberglass manufacturing operating in Batam still difficulty in face challenge related K3 problems. Although has There is K3 regulations and standards that have been determined in the fiberglass manufacturing industry. Bad his knowledge about K3 owned by the operator so can cause Health problems for employees. Based on from results of data analysis that has been carried out can be known that mark connection environment Work to disturbance health is obtained value 85.8% with that can be concluded that environment work is very influential to health problems. Can be known. The resulting RPN value is 80 points the is in the factors reason disturbance health Work that is man. With That need do purposeful improvement. For minimize happen disturbance health. Keywords: Health Disorders, K3, Industrial Revolution